Oceanic bellies and liquid feminism in Fatou Diome's Le Ventre de l'Atlantique. Issue 2 (4th March 2023) - Moji, Polo B.
ABSTRACT: Winner of the 2003 Prix des Hémisphères Chantal Lapicque, and translated into German, Italian, Portuguese, Spanish and English, Fatou Diome's 2003 novel, Le Ventre de l'Atlantique [ The Belly of the Atlantic, 2006] plays on the image of the Atlantic as an oceanic belly. This article explores the usefulness of the black Atlantic epistemology (Glissant 1990, Gilroy 1993 ) as a site for imagining the production of diasporic space, alongside the critique that 'by excluding Africa, Gilroy has in effect narrowed the Africanness or Africanity of the 'Black Atlantic' (Masilela 1996, p. 88). Through Diome's novel, I explore how this intersects with a feminist project of rendering visible the spatialization of difference, through an engagement with the geographies of domination. Borrowing from Zymunt Bauman's (2006) notion of liquid modernity, I therefore propose 'liquid feminism' as a framework that relates the globalised oceanic mobilities of African migrants to the structures of patriarchal domination which render black women's lives 'ungeographic' (McKittrick 2006 ). I start by exploring the geographic sensibility of Diome's poetics, including her use of the language of geography and her personification of the Atlantic Ocean. I then analyse how her portrayal of a g eulwaar matriclan subverts the notion of Western feminism as rescuing African women who are trapped by 'tradition'. Finally, I explore Diome's notion of 'geographic suicide' as associated with the reflexivity of African women as modern subjects a site for the 'affective mapping' (Flatley 2009 ) of diasporic identity. Ultimately, the article illustrates how Diome's feminist re-imagining of the black Atlantic centres Africa and Africanness, combating the temporal dislocation that fixes the continent as a space that is lost in the originary moment of rupture of the Middle Passage.